HACCP: An Overview - Renée Goodrich-Schneider; Keith R. Schneider; Michelle D. Danyluk; Ronald H. Schmidt (EDIS)
The acronym HACCP (pronounced /’hæ-sip/) stands for “Hazard Analysis Critical Control Point”. It is a food safety management system that is increasingly used in all aspects of the food industry. This revised 3-page fact sheet introduces the topic and summarizes the key components of a HACCP program. Written by R. Goodrich-Schneider, K. R. Schneider, M. D. Danyluk, and R. H. Schmidt, and published by the UF Department of Food Science and Human Nutrition, May 2012.